Повезло: 80 терапевтических рассказов о любви, семье и пути к самому себе / Ольга Савельева - Савельева Ольга Александровна (Эксмо, 2022)
Экземпляры: б/ф №5 (20230608) / Инвентарный номер: 41958 / Цена: / Авт.знак: С 12 / ГРНТИ: 17.82.32 / ББК: 84(2=411.2)6